PENGARUH KUALITAS PELAYA NAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI UNIT UMKM KUD KARYA MUKTI (STUDI KASUS: UNIT MINI MARKET KUD KARYA MUKTI) - Suwanti, Suwanti (IJMA (Indonesian Journal of Management and Accounting), 2021)
This study aims to determine and analyze the effect of service quality and price on purchasing decisions in the Mini Market Unit KUD Karya Mukti. This type of research is quantitative research. The data used in this study is primary data in the form of questionnaires or questionnaires given to respondents. The population in this study is the Mini Market KUD Karya Mukti consumers and the research sample is 100 respondents. Data processing in this study uses the IBM SPSS Ststistic version 21 application. The results of this study indicate that Service Quality has a positive and significant effect on purchasing decisions, Price has a positive and significant effect on purchasing decisions, Service Quality and Price simultaneously affect purchasing decisions. The value of determination of Adjusted R Square is 0.610 or 61%, so the magnitude of the influence of service quality and price variables on purchasing decisions is 0.610 or 61%, the remaining 39% is explained by other variables outside the research model